2010
DOI: 10.1037/a0019870
|View full text |Cite
|
Sign up to set email alerts
|

Life stress, maternal optimism, and adolescent competence in single mother, African American families.

Abstract: Although research demonstrates many negative family outcomes associated with single-parent households, little is known about processes that lead to positive outcomes for these families. Using 3 waves of longitudinal data, we examined how maternal dispositional optimism and life stressors are associated with parenting and child outcomes in 394 single mother African American families. Confirming prior research, we found that mothers' childhood adversities, current economic pressure, and internalizing problems we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
77
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 72 publications
14
77
0
1
Order By: Relevance
“…Optimism has also been linked to positive parenting practices. 38 These findings, linking maternal optimism to improved coping with stress and effective parenting practices, may help to explain how maternal optimism may play a role in children's behavioural development. Although dispositional optimism is a relatively stable trait, research indicates that, to some extent, optimism can be taught, 39 and therefore early intervention and parenting programmes could include content aimed at cultivating maternal optimism.…”
Section: Discussionmentioning
confidence: 96%
“…Optimism has also been linked to positive parenting practices. 38 These findings, linking maternal optimism to improved coping with stress and effective parenting practices, may help to explain how maternal optimism may play a role in children's behavioural development. Although dispositional optimism is a relatively stable trait, research indicates that, to some extent, optimism can be taught, 39 and therefore early intervention and parenting programmes could include content aimed at cultivating maternal optimism.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, these children have poor educational attainment and are more likely to become incarcerated. However, Taylor (2012) has suggested that more successful teen mothers display dispositional optimism (Taylor, Larson-Rife, Conger, Widaman, & Cutrona, 2010;Taylor et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies identified optimism as an important contributor towards the mothers' ability to adapt and cope with life stressors. Taylor's (2012) research was guided by the Family Stress Model (FSM), a paradigm that examined dispositional optimism as a characteristic that aids in decreasing perceptions of stressors and a mothers' ability to cope (Taylor et al, 2010). Additionally, important to this research is the linkage that early interventions in the mothers' lives may have contributed to the psychological wellbeing of the mothers (Taylor et al,2010;2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and Hart (2002) studied the effects of marital and non-marital union transition on health and reported similar results. Taylor et al (2010) studied life stress, maternal optimism, and adolescent competence in single mother. They emphasized on positive impacts of divorce among women who divorced in African American society and highlighted the need for further studies of processes and resources, which promote positive outcomes for African American mother-headed families and single mother families in general.…”
Section: Introductionmentioning
confidence: 99%